Upward pressure on wages and the interregional trade spillover effects under demand‐side shocks. Issue 1 (6th September 2019) - Lecca, Patrizio; Christensen, Martin; Conte, Andrea; Mandras, Giovanni; Salotti, Simone
Abstract: The paper illustrates the effect of a permanent demand‐side shock in the perturbed regions and the associated spillover effects in the non‐perturbed regions using a spatial‐numerical general equilibrium model of the EU economy. We test to what extent gradual upward pressure on wages generated by a domestic increase in demand alters the magnitude of the economic impacts in the long‐run and the degree to which this could result in changes in trade patterns. We also assess the size and the direction of the effects with varying trade substitution elasticities and under both perfectly and imperfectly competitive product markets. Resumen: El artículo ilustra el efecto de una perturbación permanente de la demanda en las regiones perturbadas y los efectos de spillover asociados en las regiones no perturbadas mediante un modelo de equilibrio general numérico‐espacial de la economía de la UE. Se comprueba hasta qué punto el aumento gradual de la presión sobre los salarios generada por un aumento de la demanda interna altera la magnitud de los impactos económicos a largo plazo y en que medida podría esto dar lugar a cambios en los patrones de comercio. También se evalúa el tamaño y la dirección de los efectos con diferentes elasticidades de sustitución comercial y bajo mercados de productos perfecta e imperfectamente competitivos. 抄録: 本稿では、EU経済の空間的数値の一般均衡モデルを用いて、摂動領域における永続的な需要側のショックの作用と、それに関連した、非摂動領域における波及効果を説明する。国内の需要増加による緩やかな賃金上昇圧が、どの程度まで長期的な経済インパクトの規模を変えるのか、そしてこれがどの程度、結果的に取引パターンの変化をもたらすかを検討する。また、完全および不完全競争製品市場の両方の条件下で、貿易の弾力性を変化させて、効果の規模と方向を評価する。